Perencanaan Manajemen Sumber Daya Manusia Lembaga Pendidikan - Endah Winarti (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
In today’s dynamic and competitive organization environment, institutions face competition, not only in physical evidence but also human resources. Humans have become a strategic factor that determines the success of an educational institution. This condition leads the importance of planning activities in the management of human resources in the institutions of education. This article aims to discuss the basic concepts of human resource planning and implementation in the institutions of education. Conceptually, human resource planning is meant as a process that involves a series of activities of forecasting and estimation in the fulfillment of the needs of the workforce, as well as a strategy for human resource development in order to achieve success. Implementation in the institution including the activities of the analysis and forecasting of projection or educators and educational needs, such as human resources inventory, projected enrollment of new learners, review goals or objectives educational institutions and ending with human resource forecasting.